TANGGUNG JAWAB HUKUM NOTARIS TERHADAP AKTA WASIAT (TESTAMENT ACTE) YANG DIBUAT DIHADAPANNYA DI KOTA PEKALONGAN - , Abdul Hafidh Ali Kelib, Agus Sudaryanto, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this research is to answer the problems regarding the legal responsibilities of a notary on the deed will (testament acte), which made front and the legal status of deed will (testament acte) open or public (openbar testament), made before a notary in the case the signing not done on each sheet preparing minutes deed by notary in Pekalongan. This was a combination of juridical normative juridical sociology, as done by way of library research to obtain secondary data relating to the deed will be supported by field studies to obtain primary data is done in the town of Pekalongan. Data obtained both secondary data and qualitative primary data was processed and then presented descriptively with elaborate and illustrate in accordance with the problems associated it the results of the study. The results showed that: (1) legal responsibilities of a notary deed will include criminal, civil and administrative, notary responsible from the beginning to the end of the notary public testament to the reading of a will, the notary profession in performing their duties are bound by legal rules that govern them, as specified in Article 16 paragraph (1) letter a UUJN in running his office notary is obliged to act in an honest, thorough, impartial independent, and safeguard the interests of parties involved in legal actions, the meaning is in the process of making a will deed the notary must act conscientiously, not siding and safeguard the interests of parties, (2) Regarding make initials in preparing minutes of each sheet of the notary public wills without the renvoi is not regulated in the Act either in UUJN or Civil Code, therefore not justified in the initial no renvoi, because it resulted in deed was not read before testamentary executor that could lead to nullification of the deed of his will. So every deed will be read and should not be only read alone by facer. In connection with the making of a will generally have clear rules that apply event-making is orderly event provided for in Article 939 Civil Code. In accordance orderly event, it was clear that the bequest should be read by a notary public without any exception.